The Luminous Child: A Critical Analysis of Qur’ānic References in Sīra Nabawiyya - Azmi, Ahmad Sanusi (Jurnal Usuluddin, 2018)
In the sīra tradition, light serves as a symbol of Prophet Muḥammad’s prophetic signs, and this concept is exemplified extensively. The sīra illustrated the Prophet as born with light, he was described as casting no shadow, even in bright sunlight or in moonlight. Interestingly, some sīra scholars have employed Qur’ānic verse as an evidentiary apparatus to substantiate the authenticity of the incident recorded in the sīra. This study aims to explore the narrative of the Prophet’s luminous condition at his birth, analyse the historical connection between the occurrence and verse 5:15 of the Qur’ān and examine hermeneutical responses of Muslim exegetes on the verse. The study is qualitative in nature in which the researcher employed both critical and analytical approaches to the works of tafsīr and sīra corpus. The study in its finding asserts that traces of a gradual development of Muslim thought, based on the specific cases from the Qur’ān. This indicates that the references they made to the Prophet Muḥammad were the result of intellectual reaction within their contemporary framework.